Analysis of pork adulteration in commercial burgers targeting porcine-specific mitochondrial cytochrome B gene by TaqMan probe real-time polymerase chain reaction - Md. Eaqub, Ali (Springer-Verlag, 2013)
Link to publisher's homepage at http://link.springer.com/